Associations between specific sleep and circadian characteristics and alcohol use disorder criteria and problems. (September 2022) - Boness, Cassandra L.; Hasler, Brant P.; Sheehan, Haley; Pedersen, Sarah L.
Highlights: Hazardous alcohol use is associated with sleep/circadian characteristics. Alcohol use disorder and sleep/circadian characteristics likely share mechanisms. Sleep interventions may be useful for reducing hazardous alcohol use. Abstract: Given the significant heterogeneity of alcohol use disorder (AUD) and the increasing priority to understand individual profiles of AUD, pursuing symptom-level examinations of AUD is important. Disturbances in sleep and circadian rhythms have demonstrated robust associations with alcohol consumption and AUD, yet little research has examined these associations at the symptom- or problem-levels and research to date has focused on one or two sleep/circadian characteristics. We sought to investigate the associations between (a) specific AUD symptoms and (b) domains of alcohol-related problems, and multiple sleep characteristics, collected at a daily level in the naturalistic environment. Young adult drinkers were recruited from the community ( N = 159, M age = 23.9, 58.5% female, 6.3% Asian, 35.9% Black or African American, 51.6% White, 5.0% multiracial) and completed a baseline visit as well as up to 18 days of naturalistic assessment. Several sleep/circadian characteristics, including eveningness, later midsleep timing, and shorter total sleep time, were consistently associated with the hazardous use symptom, above and beyond alcohol consumption. Eveningness (beta[SE] = 0.21[0.00], p <.01) was a significant predictor of the alcohol-related problem domain of role interference. Exploratory analyses did not find significant associations between sleep/circadian characteristics and cannabis-related problems. The relationship between sleep/circadian characteristics and AUD and related problems may be driven by a narrower set of symptoms, such as hazardous use and role interference. This may be due to shared mechanistic dysfunction in domains such as reward processing or cognitive control. Thus, these alcohol-related symptoms and problems may be addressed through transdiagnostic treatment approaches that target these underlying mechanisms.